Avaliação nutricional de grãos de cevada submetidos a diferentes processamentos - Novack, Mariana Moura Ercolani (2010)
Barley is one of the most economically important winter crops for the farming system in the southern Brazil and it is well-known by its high content of soluble dietary fiber (beta-glucans) which lowers plasmatic cholesterol as well as the glycemic index besides reducing the risk of colon cancer. In what concerns human consumption it has been observed recent interest for this cereal since its dietetic properties can be associated to health benefits. The aim of this research was to determine the chemical composition of barley grains under different processings, covered barley, hulless barley, hulless roasted barley, barley flakes, barley flour as well as relating the effects of the inclusion of processed barley grains as a source of fiber in diet by having Wistar rats as biological model. The grains were analyzed in relation to the dry matter content, ash, crude protein, lipids, total dietary fiber, insoluble and soluble fiber, non-fibrous carbohydrates, beta-glucans and minerals (calcium, phosphorus, magnesium, potassium, zinc, iron, manganese and copper). The bioassay was performed during 42 days; it was used 35 male Wistar rats at 21 days old, distributed in 5 treatments of 7 animals which received feed AIN-93G with varied source of dietary fiber: CONT treatment (control) with 5% cellulose; treatment CB with 5% of covered barley; treatment HB with 5% of hulless barley; treatment HRB with 5% of hulless roasted barley fiber, and treatment BF with 5% of barley flakes. It was determined: food intake, weight gain, feed conversion (FC), feed efficiency ratio (FER), multivariate bio-nutritional index (BNI), dry and wet fecal output, moisture from feces, gastrointestinal transit time, liver weight, heart weight, epididymal fat weight, kidney weight, small and large intestine weight, full and empty cecal weight as well as the following blood parameters: total proteins, albumin, hemoglobin, glucose, total cholesterol, HDL cholesterol and triglycerides. The results show significant differences among the barley grains under different processing for dry matter, ash, crude protein, dietary fiber, insoluble fiber, nonfibrous carbohydrates, calcium, potassium, magnesium, zinc, iron and manganese. Variations in the chemical composition occurred due to the effect of processing of the grain because of hullessness, stabilization, flocking and milling. The inclusion of dietary fiber of covered barley as well as of the products from its processing (hulless grain, hulless roasted grains and flakes) may be employed as source of fiber in a standard diet of AIN-93 without compromising the development of rats as well as providing less dry fecal weight, more fecal moisture and less gastrointestinal transit time, what may be attributed to more colonic fermentation.